Providing Access to Reading Comprehension for Greek Secondary Students with Mild Intellectual Disabilities - Georgios Ladias; Georgia Iatraki; Spyridon-Georgios Soulis (MDPI AG, 2022)
All students should achieve improved outcomes in academic content within general classroom and access information through reading comprehension during their daily interactions. Several adaptations and recommendations should be required for students with intellectual disabilities to access information, such as adapted texts that can provide access to reading comprehension and help them participate equally in modern society. The current study shows promise for the use of easy to read (EtR) material combined with systematic instruction, task analysis, and prompting in facilitating Greek language lessons for students with mild intellectual disabilities. Researchers used an AB single-subject design to evaluate the effects of transcribed EtR texts for providing access to information regarding grade-aligned reading comprehension in Greek language lessons. Students with mild intellectual disabilities were assessed through baseline and intervention phases and their results showed a correlational relation between the intervention supported by EtR material and the number of students' correct responses on the comprehension probes. In addition, social validity indicated the teaching intervention through adapted EtR texts as being practical and useful. Discussion of results, future research, and limitations are provided with a focus of the importance of teaching interventions based on EtR language that positively contribute to the accessibility and equality of people with intellectual disabilities to information.